Extended state observer-based finite-time guidance laws on account of thruster dynamics. (September 2019) - Duan, Meijun; Zhou, Di; Cheng, Dalin
Guidance laws are designed for a near space interceptor with line-of-sight angle as input and on–off type thrust as output. The dynamics of thruster is viewed as a first-order lag with on–off working style and is integrated with the target–interceptor engagement dynamics to design bang-bang type sliding mode guidance laws. An extended state observer is designed to estimate the line-of-sight angular rate and the acceleration of target with the line-of-sight angle as a measurement. It is rigorously proved that the states of guidance system converge to a neighborhood of sliding mode in finite time and the line-of-sight angular rate converges to a neighborhood of the origin along the sliding mode in finite time under the designed guidance laws. Furthermore, in order to reduce the switching frequency of thruster, a sliding mode guidance law with hysteresis-band according to the sufficient condition for finite time convergence is proposed. Then, it is integrated with the bang-bang type sliding mode guidance law to yield a composite guidance law. Simulation results show that the extended state observer can effectively estimate the line-of-sight angular rate and the target acceleration, and the proposed sliding mode guidance laws have better performance than typical proportional guidance law.